Endophytic fungi from kale (Brassica oleracea var. acephala) modify roots-glucosinolate profile and promote plant growth in cultivated Brassica species. First description of Pyrenophora gallaeciana - Poveda, Jorge; Rodríguez, Víctor M.; Díaz-Urbano, María; Sklenář, František; Saati-Santamaría, Zaki; Menéndez, Esther; Velasco, Pablo (Frontiers in Microbiology, 2022)
Endophytic fungi of crops can promote plant growth through various mechanisms of action (i.e., improve nutrient uptake and nutrient use efficiency, and produce and modulate plant hormones). The genus Brassica includes important horticultural crops, which have been little studied in their interaction with endophytic fungi. Previously, four endophytic fungi were isolated from kale roots (Brassica oleracea var. acephala), with different benefits for their host, including plant growth promotion, cold tolerance, and induction of resistance to pathogens (Xanthomonas campestris) and pests (Mamestra brassicae). In the present work, the molecular and morphological identification of the four different isolates were carried out, describing them as the species Acrocalymma vagum, Setophoma terrestris, Fusarium oxysporum, and the new species Pyrenophora gallaeciana. In addition, using a representative crop of each Brassica U’s triangle species and various in vitro biochemical tests, the ability of these fungi to promote plant growth was described. In this sense, the four fungi used promoted the growth of B. rapa, B. napus, B. nigra, B. juncea, and B. carinata, possibly due to the production of auxins, siderophores, P solubilization or cellulase, xylanase or amylase activity. Finally, the differences in root colonization between the four endophytic fungi and two pathogens (Leptosphaeria maculans and Sclerotinia sclerotiorum) and the root glucosinolate profile were studied, at different times. In this way, how the presence of progoitrin in the roots reduces their colonization by endophytic and pathogenic fungi was determined, while the possible hydrolysis of sinigrin to fungicidal products controls the colonization of endophytic fungi, but not of pathogens.